Uncommon World Production: In Search of Freedom and Recognition - Antonio A. R. Ioris (Societies)
The socio-spatiality of capitalist modernity is the embodiment of pressures to eliminate common, spatially adapted institutions in the name of an allegedly more rational world demarcated by the prospect of having everything private and predisposed to be exploited. The vital element of these pressures to legitimise economic inequalities to extract more and more value from labour and nature is the phenomenon of uncommoning. This article has several interconnected goals, especially, an interpretation of the meaning and practices of uncommoning—making use of classical, contemporary, and decolonial academic and grey literature—and a critical reflection on the frontiers of the modern world, where uncommoning is clearly the key socio-spatial driving force underpinning a deceitful democracy and providing justification for the encroachment of private properties upon the commons. This focus on the commons facilitates and radicalises the comprehension of how societies and communities deal with the allocation, use, and preservation of cherished elements of their material and immaterial reality. It can be constructively reached from the perspective of Global South societies, indigenous nations in particular, with solid experiences and knowledge of the commons. They have the outstanding intellectual and moral authority, and the main job for most is to listen, learn, and act together.